Impact of light rail implementation on labor market accessibility: A transportation equity perspective - Yingling Fan; Andrew E Guthrie; David M Levinson (Journal of Transport and Land Use)
This study seeks to examine transit’s role in promoting social equity by assessing before-after impacts of recent transit changes in the Twin Cities, including opening of the Hiawahta light rail line, on job accessibility among workers of different wage categories. Geo-spatial, descriptive and regression analyses find that proximity to light rail stations and bus stops offering direct rail connections are associated with large, statistically significant gains in accessibility to low-wage jobs. These gains stand out from changes in accessibility for the transit system as a whole. Implications of the study results for informing more equitable transit polices are discussed.